2000
DOI: 10.1021/bi000362j
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Saccharomyces cerevisiae Ribosomal Stalk:  Binding of P1 Proteins Is Required for the Interaction of P2 Proteins

Abstract: The yeast ribosomal stalk is formed by a protein pentamer made of the 38 kDa P0 and four 12 kDa acidic P1/P2. The interaction of recombinant acidic proteins P1 alpha and P2 beta with ribosomes from Saccharomyces cerevisiae D4567, lacking all the 12 kDa stalk components, has been used to study the in vitro assembly of this important ribosomal structure. Stimulation of the ribosome activity was obtained by incubating simultaneously the particles with both proteins, which were nonphosphorylated initially and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
40
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
(60 reference statements)
9
40
2
Order By: Relevance
“…Protein P0 seems to be able to directly interact only with the P1 proteins as shown previously by ribosome reconstitution tests (58) and double hybrid data (36), and it is possible, therefore, that a direct interaction between P0 and the P2 proteins may not exist in the ribosome. There are at least two ways in which P1␣⅐P2␤ and P1␤⅐P2␣ can be assembled in the stalk (Fig.…”
Section: Figsupporting
confidence: 57%
“…Protein P0 seems to be able to directly interact only with the P1 proteins as shown previously by ribosome reconstitution tests (58) and double hybrid data (36), and it is possible, therefore, that a direct interaction between P0 and the P2 proteins may not exist in the ribosome. There are at least two ways in which P1␣⅐P2␤ and P1␤⅐P2␣ can be assembled in the stalk (Fig.…”
Section: Figsupporting
confidence: 57%
“…There is also a consensus for an anchorage of the P1/P2 dimer by a direct interaction of the P1 N-terminal domain, but not the P2 N-terminal domain with P0 (Gonzalo et al, 2001;Shimizu et al, 2002;Zurdo et al, 2000).…”
Section: Binding Of P1/p2 Dimers (And Equivalents) To P0 (And Equivalmentioning
confidence: 99%
“…P0 has the same 11-amino acid C-terminal sequence as P1 and P2, and the phosphorylation site, Ser-302 in P0, is within this conserved C terminus. Examination of the stalk assembly both in vivo and in vitro has revealed that P2␤ is unable to bind to the ribosome in the absence of P1␣; in contrast P1␣ is capable of binding to the particle in the absence of P2␤ (13). These results have been interpreted to suggest that assembly of the stalk complex is a coordinated process in which P1 proteins provide anchorage to the ribosome for the P2 proteins, whereas the P2 proteins confer functionality to the complex (13).…”
mentioning
confidence: 99%
“…Examination of the stalk assembly both in vivo and in vitro has revealed that P2␤ is unable to bind to the ribosome in the absence of P1␣; in contrast P1␣ is capable of binding to the particle in the absence of P2␤ (13). These results have been interpreted to suggest that assembly of the stalk complex is a coordinated process in which P1 proteins provide anchorage to the ribosome for the P2 proteins, whereas the P2 proteins confer functionality to the complex (13). Recent evidence has also shown that the heterodimer P1␣-P2␤ is a stable entity in solution; this observation led to the proposal that the P proteins form dimers in the cytoplasm prior to assembly on the ribosome (14).…”
mentioning
confidence: 99%